Effect Of Managing Fertilizer Types And Dosages Of Kno3 On Plant Growth And Results Red Onion (Allium ascalonicum L) - Suprapti, Endang; Budiyono, Agus; Supriyadi, Teguh; Dewi, Tyas Soemarah Koernia; Bayu, Tejo (Agribusiness Department, Agriculture Faculty, Tunas Pembangunan University, Surakarta, Indonesia, 2023)
This research was carried out on the basis of the increasing national market need for shallots while production still needs to be increased. This research was carried out from August 2022 to October 2022 in Semono Hamlet, Tempursari Village, Sambi District, Boyolali Regency. Altitude 184 above sea level, soil pH 6, Vertisol soil type (PPT = Grumosol). This study used a Complete Randomized Block Design (RAKL) consisting of two factors, the first factor being the type of manure which is divided into three levels, namely Fermentation of Chicken Manure, Fermentation of Goat Manure, Fermentation of Cow Manure ( P1, P2, P3). The second factor is the dose of KNO3 fertilizer which is divided into three levels, namely dose 75 kg/ha, dose 150 kg/ha, and dose 225 kg/ha (K1, K2, K3). each with 3 replications. The parameters observed in this study were the response of shallot plants to each type of manure to the addition of KNO3 fertilizer including Growth Parameters which included plant height, number of tillers (Kaplings), Fresh Stove Weight, and Stove Weight dry while the plant yield parameters include wet tuber weight per sample (g), dry tuber weight per sample (g), tuber wet weight per plot (g), tuber dry weight per plot (g), tuber diameter (cm) to determine the most effective dosage of manure in combination with KNO3 doses to increase shallot crop yields. The results showed that the KNO3 dose of 225 kg/ha had a significant effect on the parameters of wet stover weight and dry stover weight.